2016
DOI: 10.5455/ijmsph.2016.16112015261
|View full text |Cite
|
Sign up to set email alerts
|

Association of thyroid disorders in females with primary infertility attending a tertiary-care hospital in northeast India

Abstract: Background: A close interconnection is present between hypothyroidism and hyperprolactinemia. Failure to ovulate regularly in women of the reproductive age group may occur owing to hypothyroidism. Objective: To look for thyroid disorders among the primary infertile group of female patients and to see the association of serum prolactin level and thyroid-stimulating hormone (TSH) level, if any. Materials and Methods: In this study, we investigated 53 diagnosed female subjects of primary infertility who were sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…29 In this study, non-significant results of TSH, fT 4 and fT 3 were exhibited between the groups which may be because of the fact that majority of the participants exhibited the normal thyroid functions (i.e euthyroid state). Similar to our findings statistically non-significant results regarding thyroid dysfunction were also observed among fertile and infertile females 7,31 while statistically significant results of raised T 3 , T 4 32 and raised TSH level 4,21 were reported in primary infertile groups. In accordance to current study, statistically nonsignificance difference in terms of TSH between primary infertile and fertile groups was also compatible with the findings of Shalev et al and Buyru et al as cited by Sahin A and Onder F. 15 Significant positive correlation was observed between fT 3 and fT 4 (p=0.002, r = 0.330) 15 which was also similar to present findings in primary infertile females (p=0.000, r = 0.684).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…29 In this study, non-significant results of TSH, fT 4 and fT 3 were exhibited between the groups which may be because of the fact that majority of the participants exhibited the normal thyroid functions (i.e euthyroid state). Similar to our findings statistically non-significant results regarding thyroid dysfunction were also observed among fertile and infertile females 7,31 while statistically significant results of raised T 3 , T 4 32 and raised TSH level 4,21 were reported in primary infertile groups. In accordance to current study, statistically nonsignificance difference in terms of TSH between primary infertile and fertile groups was also compatible with the findings of Shalev et al and Buyru et al as cited by Sahin A and Onder F. 15 Significant positive correlation was observed between fT 3 and fT 4 (p=0.002, r = 0.330) 15 which was also similar to present findings in primary infertile females (p=0.000, r = 0.684).…”
Section: Resultssupporting
confidence: 89%
“…Quantitative estimation of TSH, fT 4 and fT 3 levels was done by using chemiluminescent Microparticle Immunoassay (CMIA) technology (Abbott / ARCHITECT i1000SR) accompanying a flexible assay known as Chemiflex. 7,28 The commercial kits used in the laboratory of Madinah Teaching Hospital were 7K63 ARCHITECT for fT 3 , 7K65 ARCHITECT for fT 4 and 7K62 ARCHITECT for TSH estimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nath el al. [10] found a positive correlation between serum TSH and prolactin level among the females subject in the northeast part of India kaur et al [2] in their research concluded that the serum prolactin level rises in relation to rising level of serum TSH in the patients suffering from hypothyroidism.…”
Section: Discussionmentioning
confidence: 92%
“…Failure to ovulate regularly in women of the reproductive age group may occur owing to hypothyroidism. 8 Hyperprolactinemia badly affects the fertility possibility by ruining the pulsatile secretion of gonadotropin releasing hor-mone (GnRH), thereby interfering with ovulation. This is implicated in menstrual and ovulatory dysfunctions such as amenorrhea, oligomenorrhea, anovulation, inadequate corpus luteal phase, and galactorrhea.…”
Section: Introductionmentioning
confidence: 99%